A rare presentation of adrenal adenoma in infancy: isolated Cushing`s syndrome - Şal, Oğuzhan; Yeğen, Gülçin; Oğuzkurt, Pelin (The Turkish Journal of Pediatrics, 2020)
Adrenocortical tumors are rare in children. Most of these tumors present with endocrinological manifestations, majority of which with virilizing features alone or in combination with over production of other adrenal hormones. However, it is uncommon of an adrenocortical tumor to present solely with Cushing`s syndrome. In this paper we discuss the clinical presentation and management of a 5-month-old infant who had presented with Cushing`s syndrome due to a functioning adrenocortical adenoma without androgen and mineralocorticoid excess, and made a brief review on the clinical and histopathological characteristics of adrenocortical tumors.